Self-reported exposure to hazards and mitigation strategies among oil and gas extraction workers in three U.S. states. Issue 10 (2nd November 2022) - Wingate, Kaitlin C.; Scott, Kenneth A.; Pratt, Stephanie; King, Bradley; Esswein, Eric J.; Ramirez-Cardenas, Alejandra; Snawder, John; Hagan-Haynes, Kyla
Abstract: Numerous health and safety hazards exist at U.S. onshore oil and gas extraction worksites. Higher fatal injury rates have been reported among drilling and servicing companies, which are more likely to employ workers in construction and extraction occupations, compared to operators that employ more workers in management and office and administrative support roles. However, there is little information describing the extent to which workers encounter these hazards, are provided hazard mitigation strategies by their employers, or use personal protective equipment (PPE). A cross-sectional survey of 472 U.S. oil and gas extraction workers was conducted to identify and characterize factors related to on-the-job fatalities, injuries, and illnesses and determine workers' health and safety concerns. Workers were employed by servicing companies (271/472, 57.4%), drilling contractors (106/472, 22.5%), and operators (95/472, 20.1%). The likelihood of contact with hazardous substances varied by substance and company type. Drilling and servicing employees had significantly higher odds of self-reported contact with pipe dope (ORdrilling = 10.07, 95% CI: 1.74–63.64; ORservicing = 5.95, 95% CI: 2.18–18.34), diesel exhaust (ORdrilling = 2.28, 95% CI: 1.15–5.05; ORservicing = 4.93, 95% CI: 2.73–10.32), and drilling mud (ORdrilling = 24.36, 95% CI: 4.45–144.69; ORservicing = 3.48, 95% CI: 1.24–12.20), compared to operators. Safety policies, programs, and trainings were commonly reported by workers, although substance-specific training (e.g., respirable crystalline silica hazards) was less common. Differences in self-reported employer PPE requirements and worker use of PPE when needed or required for safety highlight a need for novel strategies to improve the use of PPE. Overall, this study highlights differences in work conditions by company type and uncovers gaps in employer administrative controls and PPE use.